2018
DOI: 10.21511/ppm.16(4).2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Classification and prioritization of stakeholders’ information requests according to Sustainable Development Goals: case of cross-sector partnership in Ukrainian food production industry

Abstract: Tracking progress in Sustainable Development Goals (especially Goal 2, Goal 17) substantiates the classification of stakeholders information requests in different sectors of the economy, as well as development of algorithms for selecting the most priority and relevant requests in the context of stakeholder cross-sector partnership. Capital concept and multi-stakeholder approach were recognized as the most appropriate for solving these tasks. This research of existing categories and groups of stakeholders in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A recent global survey found that integrating CE application into business can boost innovation, help companies become more efficient and competitive in many areas such as resource management, product development, and production processes (WBCSD, 2018). From the social aspect, within internal (Penz & Polsa, 2018;Sukhonos et al, 2018) and external (Padilla-Rivera et al, 2020) stakeholder participation, CE adoption plays an important role in addressing problems that arise from business operational activities as acceptable, transparent, and multi-orientation ways that enable innovation for circularity. The implementation of CE framework that focuses on environmental improvement made good business and business increasingly use CE as their strategic approach (Donner & de Vries, 2021;PWC, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent global survey found that integrating CE application into business can boost innovation, help companies become more efficient and competitive in many areas such as resource management, product development, and production processes (WBCSD, 2018). From the social aspect, within internal (Penz & Polsa, 2018;Sukhonos et al, 2018) and external (Padilla-Rivera et al, 2020) stakeholder participation, CE adoption plays an important role in addressing problems that arise from business operational activities as acceptable, transparent, and multi-orientation ways that enable innovation for circularity. The implementation of CE framework that focuses on environmental improvement made good business and business increasingly use CE as their strategic approach (Donner & de Vries, 2021;PWC, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific community has made a significant progress in identifying corporate competitive strategies [1][2][3][4][5][6][7] and instruments of company activities' ecologization [9][10][11]. A number of authors noticed that company's competitiveness results from providing socioeconomic macro-level policy [12][13][14][15][16][17][18][19][20]. A significant number of scientific schools investigate the features of energy policy and the ways and mechanism of implementing renewables [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The 2030 Agenda for Sustainable Development, adopted by the UN member states in 2015, is gradually forming the general trend of conducting economic research on achievement of the goals defined in the document, some researchers also considered the issue of ensuring sustainability financial performance of agriculture companies and analyzed its determinants (Wei et al, 2017;Sukhonos et al, 2018;Sokil et al, 2020;Makarenko et al, 2021;Alrowwad et al, 2022).…”
mentioning
confidence: 99%